A military history of Afghanistan : from the Great Game to the Global War on Terror - Jalali, Ali Ahmad (Modern war studies., 2017)
The first comprehensive history of the last two-plus centuries of warfare and international conflict in land-locked Afghanistan, from the Anglo-Afghan wars of the 1800s through the region's early 20th-century struggles to modernize, its last monarchy (1933-1973), the Soviet Union's so-called "Vietnam War" in the 1980s, and America's "War on Terror," which began in 2001 and continues into the present. By an insider native Afghan author whose careers have encompassed military, government, and academic service.